Research Trends on Artificial Intelligence Led Investors’ Behaviour in Gold Bullion Market: Bibliometric Analysis Using R Studio and VOSviewer - Sirisha Charugulla (International Journal of Intelligent Systems and Applications in Engineering, 2024)
The study conducted a bibliometric examination of investors' behaviour using AI in gold bullion market research publications published between 1994 and 2024 using the Scopus database. The study performed the analysis of science mapping and performance on paper from the last three decades of publications. The study makes use of bibliometrics, science mapping, and performance analysis on 548 publications from the Scopus database. This study looked at Thematic mapping, co-citations, co-occurrence of keywords, productive authors, cooperation between writers and nations, citable documents, most pertinent institutions, and cited countries, and scientific output of papers. Bibliometric-Biblioshiny, R package and Vosviewer were the instruments utilized in the study to conduct the science mapping analysis and performance analysis. There were 50 citations for each document or 22.62 citations per year for each document. China, USA, India, and France are the most fruitful nations related to total citations and international partnerships. Resources Policy, International Review of Financial Analysis, Energy The leading journals for investor behaviour utilizing AI in gold market research.